(untitled) (World Economics and Finance Bulletin, 2025)
This article substantiates the importance of using the Australia’s experience in developing financial support for business entities in order to promote the growth of an innovation economy in Uzbekistan. Based on the Australian practice, the scientific and theoretical conclusions of Australian, CIS (Russian), and local scholars have been analyzed. The key elements of the Australia’s experience have been examined, and the country’s position in the 2024 Global Innovation Index has been reviewed